International taxation of dividends reconsidered in light of corporate tax integration : proceedings of a seminar organised jointly with the OECD in Toronto in 1994 during the 48th Congress of the International Fiscal Association.: proceedings of a seminar organised jointly with the OECD in Toronto in 1994 during the 48th Congress of the International Fiscal Association. (2016) - Unknown
No abstract available